FEATURES OF EMOTIONALLY-PERSONAL SPHERE IN PATIENTS WITH SHARP DECREASE OF VISUAL FUNCTIONS - A. A. Shchuko; I. V. Yaroslavtseva; T. N. Yurieva (Acta Biomedica Scientifica, 2014)
The aim of the work was to reveal features of emotionally-personal sphere in patients with sharp decrease of visual functions. We studied emotionally-personal features of 37 patients. The main group included 18 patients with sharp decrement in visual acuity down to 0,001 in consequence of the retinal detachment, hemophthalmia and eye thrombosis at 1-2 months term before the examination. Control group included 19 patients without eye pathology. Obtained results show that patients with sharp decrease of visual functions have emotionally-personal features that influence their quality of life.